مدى توافر الكفايات التعليمية لمعلمات رياض الأطفال في ضوء مبادئ إدارة الجودة الشاملة "دراسة ميدانية في مدينة دمشق" - مراد سمير; شريف مها (مجلة جامعة تشرين للبحوث والدراسات العلمية- سلسلة الآداب والعلوم الانسانية, 2018)
يهدف هذا البحث إلى التعرف على مدى توافر الكفايات التعليمية لمعلمات رياض الأطفال في ضوء مبادئ إدارة الجودة الشاملة, ولتحقيق أهداف البحث تمّ تصميم بطاقة ملاحظة, وتطبيقها على عينة من معلمات رياض الأطفال في مدينة دمشق بلغت /124/ معلمة,وبعد الدراسة والتحليل تمّ التوصل إلى النتائج التالية: 1- تتمتع معلمة الروضة بقدر واف من الكفايات الشخصية التي تجعلها قادرة على التعامل مع الأطفال بشكل يرقى بهم إلى المستوى المطلوب وبما يحقق مبادئ الجودة الشاملة. 2- تعاني معلمات الروضة من ضعف في بعض الكفايات التعليمية وخاصة تلك المتعلقة بعملية تقويم الطفل واستخدام الأجهزة والتقنيات التعليمية الحديثة والإلمام بخصائص نمو الأطفال الوجداني. 3- وجود فروق ذات دلالة إحصائية بين معلمات الروضة في مدى توافر الكفايات التعليمية تبعاً لمتغيرات المؤهل العلمي, سنوات الخبرة, الدورات التدريبية. This study deals with the availability of teaching efficiencies to kindergarten teachers in the light of the principles of comprehensive quality management. To fulfill the aims of this research, an observation card is designed for and applied to a sample of /124/ kindergarten teachers in Damascus. After studying and analyzing the data used, the following findings are obtained: - Kindergarten teachers have a sufficient amount of personal efficiencies which enable them to deal with children in a way that places them at the required level and meets the principles of comprehensive quality. - Kindergarten teachers lack some teaching efficiencies, especially those related to the process of evaluating children, the use of modern teaching devices and techniques, as well as familiarization with the characteristics of children’s emotional growth. - The presence of statistical significance differences among kindergarten teachers in the availability of teaching efficiencies according to variations in academic qualifications, years of experience, and training programmes.